Pengaruh Ketetapan Waktu dan Tarif Pengiriman Terhadap Kepuasan Pelanggan Pengiriman J&T Express Tanah Tinggi - Evitha, Yuli; sari, Sukarni Novita (JAMBIS : Jurnal Administrasi Bisnis, 2025)
In the current era of globalization, the development of businesses engaged in the freight forwarding industry is increasingly rapid. Punctuality and Shipping Rates are important to affect customer satisfaction. This study aims to measure the Effect of Punctuality and Delivery Rates on Customer Satisfaction of PT J&T Express Tanah Tinggi Delivery.This study uses a quantitative method with a sample of 100 respondents. In this study, data analysis techniques were used in the form of statistics with data testing using validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, t tests, coefficient correlation tests, determination coefficient (R2) tests, and f-tests. The calculation shows that it is larger than the calculation of table 1.986 which means that each independent variable has a partial effect on the bound variable. In the f test, the results of f calculation were simultaneously obtained of 46.333 greater than f in table 3.10 so that it can be concluded that Punctuality and Delivery Rates have an influence on Customer Satisfaction.